Visualization of stimulus‐specific heterogeneous activation of individual vascular smooth muscle cells in aortic tissues. Issue 1 (14th July 2017) - Komatsu, Satoshi; Kitazawa, Toshio; Ikebe, Mitsuo
Abstract : Intercellular communication among autonomic nerves, endothelial cells (ECs), and vascular smooth muscle cells (VSMCs) plays a central role in an uninterrupted regulation of blood flow through vascular contractile machinery. Impairment of this communication is linked to development of vascular diseases such as hypertension, cerebral/coronary vasospasms, aortic aneurism, and erectile dysfunction. Although the basic concept of the communication as a whole has been studied, the spatiotemporal correlation of ECs/VSMCs in tissues at the cellular level is unknown. Here, we show a unique VSMC response to ECs during contraction and relaxation of isolated aorta tissues through visualization of spatiotemporal activation patterns of smooth muscle myosin II. ECs in the intimal layer dictate the stimulus‐specific heterogeneous activation pattern of myosin II in VSMCs within distinct medial layers. Myosin light chain (MLC) phosphorylation (active form of myosin II) gradually increases towards outer layers (approximately threefold higher MLC phosphorylation at the outermost layer than that of the innermost layer), presumably by release of an intercellular messenger, nitric oxide (NO). Our study also demonstrates that the MLC phosphorylation at the outermost layer in spontaneously hypertensive rats (SHR) during NO‐induced relaxation is quite high and approximately 10‐fold higher than that of its counterpart, the Wister–Kyoto rats (WKY), suggesting that the distinct pattern of myosin II activation within tissues is important for vascular protection against elevated blood pressure. Abstract : Impairment of intercellular communication between endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) is linked to development of vascular diseases such as hypertension, cerebral, and coronary vasospasms, aortic aneurism, and erectile dysfunction. Here we show a unique VSMC response to ECs during contraction and relaxation of isolated aorta tissues through visualization of spatiotemporal activation patterns of smooth muscle myosin II.